2009
DOI: 10.2465/jmps.090611
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of metasomatized peridotites above subducting slab: a case study of hydrous metaperidotites from Happo-O'ne complex, central Japan

Abstract: Hydrous peridotites from the Happo -O'ne area in central Japan, which form a serpentinite mélange in the high -P/T Renge metamorphic belt, vary from depleted lherzolites to harzburgites with subordinate dunite that contains primary chromian spinel with Cr# = 0.72 on average. Systematic variations of major and trace elements of bulk -rock compositions possibly resulted from various degrees of partial melting experienced by their protoliths (15% to <30% fractional melting). Some hydrous peridotites from the trem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
(36 reference statements)
2
11
0
Order By: Relevance
“…Low-degree batch melting (E2 event) could not influence the REE (especially the HREE) and HFSE contents sufficiently. An increased content in Cs and Ba is usually interpreted as an impact of slab-derived (metamorphic) fluids (Scambelluri et al 2004;Khedr and Arai 2009). Therefore these signatures in the studied samples should be the result of the E3 and E4 events.…”
Section: Chemical Changes Between "Pyrolite" and The Dark Cpx Harzburmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-degree batch melting (E2 event) could not influence the REE (especially the HREE) and HFSE contents sufficiently. An increased content in Cs and Ba is usually interpreted as an impact of slab-derived (metamorphic) fluids (Scambelluri et al 2004;Khedr and Arai 2009). Therefore these signatures in the studied samples should be the result of the E3 and E4 events.…”
Section: Chemical Changes Between "Pyrolite" and The Dark Cpx Harzburmentioning
confidence: 99%
“…Perovskite was however also found from medium-to low-temperature reaction domains between the chemically contrasting rocks metamorphosed in blueschist to eclogite facies, as reported further. Alteration and reaction-metasomatic zones in ultramafics are reliable indicators of fluid-rock interaction processes (Grégoire et al 2001;Scambelluri et al 2004Scambelluri et al , 2006Khedr and Arai 2009;Kodolányi et al 2012;Uysal et al 2012). For example, abyssal peridotites are generally strongly affected by oceanic (seafloor) hydrothermal alterations like serpentinization (Bodinier and Godard 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our samples, enriched in LREE(La,Ce), Cs, ±Ba, U, Nb, Pb, As, Sb, ±Nd and Li in comparison with HREE, Rb and Sr (Fig. 7a, b) can therefore be interpreted as having been overprinted by slab-derived metamorphic fluids (e.g., Scambelluri et al 2004Scambelluri et al , 2014Khedr & Arai 2009;Putiš et al 2012). Our LA-ICP-MS mineral study revealed behaviour of trace elements during the harzburgite alterations in relationship to Prv genesis.…”
Section: G G G G Geol Eol Eolmentioning
confidence: 93%
“…Element mobility in accretionary wedges using the LA-ICP-MS data was searched, for example, by Scambelluri et al (2004Scambelluri et al ( , 2014 and Khedr & Arai (2009) in HP peridotites and serpentinites with implications for fluid processes and trace-element recycling. Kodolányi et al (2012) investigated fluid-rock interaction processes in ocean floor and fore-arc serpentinites.…”
Section: Introductionmentioning
confidence: 99%
“…CaCa-NaNa- Ishizuka, 1980Ishizuka, , 1987 Na Type 2 Na K , Ozawa, 1988;Ohara and Ishii, 1998;Zanetti et al, 1999;Chen and Zeng, 2007;Spandler et al, 2008 Khedr andArai 2009 , Na Evans, 1977Arai, 1975, 1984;Nozaka, 2003Nozaka, , 1951Fujimaki and Yomogida, 1986 …”
mentioning
confidence: 99%